Micro-credential in integrated and sustainable urban farming: farm design - Abu Bakar, Aniza; Amid, Azura; Abdullah Sidek, 'Atiah (2021)
The course module intends to introduce the technique to plan and design the garden/farm area. The participants of the course will be able to plan to design their garden/farming layout optimally